ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN PADA CV MITRA USAHA MANDIRI CABANG BOGOR - Adissa Jasmiena Putri (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The aim of conducting this research is to find out whether the sales accounting information system is running well or not. The data analysis used used qualitative methods. From the results of the research carried out, the sales accounting information system at CV Mitra Usaha Madiri is running well, every part and equipment of the company is responsible according to their respective positions. Supporting documents such as sales invoices and delivery letters are appropriate and in sequence according to the transaction sequence. The sales process carried out is modern using a web database so it is easy to access anywhere and at any time. However, there is one drawback or weakness, namely, CV Mitra Usaha Mandiri carries out dual functions between sales admin and cashier. So the customer service provided may cause delays in service and the website often lags when it is being used. So in this research, it is recommended that companies recruit additional employees in the cashier and IT departments to streamline websites that are experiencing problems. This is done so that company control runs more quickly, accurately and relevantly.